Targeting the IL‐4/IL‐13 signaling pathway sensitizes Hodgkin lymphoma cells to chemotherapeutic drugs. Issue 8 (25th April 2013) - Natoli, Antonino; Lüpertz, Regine; Merz, Christian; Müller, Wolfgang W.; Köhler, Rebecca; Krammer, Peter H.; Li‐Weber, Min
<x xml:space="preserve">Abstract</x> Hodgkin/Reed‐Sternberg lymphoma (HL) is a clonal B‐cell‐related malignancy. Although many patients with HL can be cured by the current regimen of high‐dose multi‐agent chemotherapy, the treatment causes high risks of later pathologies including secondary malignancies. This fact highlights the demand to develop rational treatment for HL. Survival and growth of HL cells are largely dependent on their microenvironment. In this study, using the HL cell lines L1236 and KM‐H2 as model systems, we investigated the role of IL‐4/IL‐13 signaling in regulation of drug sensitivity and resistance in HL. We show that specific blocking of IL‐4 and IL‐13‐mediated STAT6 activation by either an IL‐4‐binding fusion protein APG598 or an IL‐4R antagonist APG201 (R121D/Y124D) renders HL cells more prone to apoptotic killing by chemotherapeutic drugs such as Mitomycin C, 5‐Fluorouracil, Etopside, Doxorubicin and Paclitaxel. This effect is due to inhibition of STAT6‐mediated elevation of expression of the anti‐apoptotic Bcl‐2 family protein Bcl‐xL. Employing ChIP analysis in combination with APG201 or STAT6‐specific siRNA we identified a defined STAT6‐binding site in the Bcl‐xL promoter region from −1967 to −1957 of the transcription start site. Our data demonstrate that the IL‐4/IL‐13‐STAT6‐Bcl‐xL axis may be an important target for HL treatment. This study also suggests that combination of classical chemotherapeutic drugs with the IL‐4/IL‐13 antagonists may enhance efficacy and reduce risks of toxicity from high dose of drugs in HL treatment.